Biomechanical thrombosis: the dark side of force and dawn of mechano-medicine - Yunfeng Chen; Lining Arnold Ju (Stroke and Vascular Neurology, 2020)
Arterial thrombosis is in part contributed by excessive platelet aggregation, which can lead to blood clotting and subsequent heart attack and stroke. Platelets are sensitive to the haemodynamic environment. Rapid haemodynamcis and disturbed blood flow, which occur in vessels with growing thrombi and atherosclerotic plaques or is caused by medical device implantation and intervention, promotes platelet aggregation and thrombus formation. In such situations, conventional antiplatelet drugs often have suboptimal efficacy and a serious side effect of excessive bleeding. Investigating the mechanisms of platelet biomechanical activation provides insights distinct from the classic views of agonist-stimulated platelet thrombus formation. In this work, we review the recent discoveries underlying haemodynamic force-reinforced platelet binding and mechanosensing primarily mediated by three platelet receptors: glycoprotein Ib (GPIb), glycoprotein IIb/IIIa (GPIIb/IIIa) and glycoprotein VI (GPVI), and their implications for development of antithrombotic ‘mechano-medicine’ .